Economic Survey of Latin America and the Caribbean 2022 - Economic Commission for Latin America; the Caribbean (United Nations, 2023)
The 2022 edition of the Economic Survey of Latin America and the Caribbean outlines the region’s economic performance in 2021 and analyses trends in the early months of 2022, as well as the outlook for growth for the year. It examines the external and domestic factors that have influenced the region’s economic performance in 2021, trends for 2022, and how these factors will affect economic growth in the coming years. This edition also presents some of the main challenges the region faces in investing for sustainable and inclusive economic growth. It analyses the trends in total investment over the last 70 years and highlights the profound change brought about by the 1980s debt crisis, with a slowdown in investment from the 1990s onwards.